Our architecture - Tajuddin Rasdi (Gerakbudaya essentials, 2020)
Still relevant despite the passage of time, Tajuddin Rasdi⁰́₉s musings on the state of architecture in Malaysia remain essential readings for both experts and the public. There remains a relative lack of public discourse on architecture, since much of it circulates within the professional sector and academia. Here, the author presents blueprints for better architecture in a fast-changing milieu, studying practical, environmental and cultural facets. By discussing everything from shopping malls to the revival of ornamentation, this collection allows us to think more broadly about the kind of architecture that best suits a New Malaysia.